Catheter-based distal sciatic nerve block in patients with Charcot-Marie-Tooth disease - Schmitt, Heike; Huberth, Sandra; Huber, Horst; Münster, Tino (BMC Anesthesiology, 2014)
The use of peripheral nerve blocks in patients with Charcot-Marie-Tooth (CMT) disease is scarcely reported; however, when performed it has proven to be effective for postoperative pain control.A distal catheter-based sciatic nerve block for postoperative pain control was offered to 27 consecutive CMT patients scheduled for elective foot surgery. 18 of the 27 CMT patients consented to the offered sciatic nerve block. Localization of the sciatic nerve was guided by a nerve stimulator. The threshold current required to generate a motor response was assessed and a catheter inserted. Postoperative pain was assessed by recording the dose of analgesics to maintain visual analog score < 3 the next 48 hours. On demand patients received boluses of ropivacaine (2 mg/mL) via the catheter and/or analgesics in case of insufficient pain relief. Total postoperative ropivacaine dosage and analgesic consumption were recorded. About one year after the block patients were contacted to report their actual status by self-assessment.In 17 patients a catheter could be placed. In 7 patients placement of the catheter was difficult (several attempts, high electrical impedance). Patients with nerve block had lower analgesics consumption compared to patients without a block. Surprisingly, the 7 patients with "difficult" catheter-placement had the overall lowest ropivacaine and analgesics consumption compared to all other patients with or without peripheral block. No anesthesia related complications were reported by the questionnaire.In our small series catheter-based distal sciatic block within CMT patients had safely been used for pain relief up to three days. The infusion of local anesthetics via a catheter was not associated with any complication.
EVALuna2:16671